Modeling in fluid mechanics : instabilities and turbulence - Gaissinski, Igor; Rovenskii, Vladimir Y., 1953- (CRC Press, Taylor and Francis Group, 2018)
"This volume is dedicated to modeling in fluid mechanics and is divided into four chapters, which contain a significant number of useful exercises with solutions. The authors provide relatively complete references on relevant topics in the bibliography at the end of each chapter."--Provided by publisher.